Like-love-hate + ing - Flores De La A, Anthony Mauricio (2022)
A good teacher is one who guides his students on the right path. all students need a good teacher who is capable of teaching in different ways with the aim of transmitting their knowledge to the students. Demonstration classes are the best way to show that we are prepared to educate new generations in all areas such as class control, choosing a good methodology, good use of technology, being prepared for any unexpected situation, and above all looking for the best way for students to learn. This demonstrative class has given me the practice to understand what I am going to face in the workplace and to continue preparing myself every day to be a better teacher.